CONFLITO GERACIONAL E A IDENTIDADE DOS JOVENS ADVENTISTAS DO SÉTIMO DIA: NEGAÇÃO OU RECONSTRUÇÃO DA IDENTIDADE ADVENTISTA POR PARTE DOS JOVENS - Martins, Rafael Malisani (2012)
This present study aims to examine the generational gap and identity formation of young Adventists, in order to verify if the generational gap is a demonstration that young people are breaking with the church or, reconstructing identity. The generational gap can be seen in various spheres of society and even within the Adventist Church. However, the generational gap is not caused by rebellion, but for different ways to react and cope with the characteristics of contemporary society. Thus, older people do not agree with the new proposals of young people and also not even the youngest wish to continue living with the old stuff. The Adventist Church has experienced the generational gap in two main aspects: The first is evident in the communication, the second in the worldview of the world. The language has changed in the time to communicate, in the present context, the image took the words function. Therefore, communication may not reach your goal, especially the younger ones, when expressed only through words. The other aspect that has caused the conflict is the world concept to the youngest. For them, the world is not synonymous with sin as some older people understand. Because of this difference, certain issues are not acceptable within the church, because they are linked to the world and the world is understood as sin. However, my conclusion is that though the young do not understand the world itself as a sin, they understand that there are aspects of the world that are wrong. These aspects are not acceptable to them and therefore they do not wish to break with the church. But they are looking for significant changes that fit with their worldview. It s possible to show this same line of reasoning in some church leaders, but the reports of young people express that did not reach the local practice. Once I conceive the Hervieu-Leger s thought that identity is not passed intact from father to son, but built individually, I understand that young people are forming their own identity. For this identity to be solidly formed on the Adventists principles and opened to the necessary changes in society, it does, in my perception, need to re-read Ellen White based on the thought of Walter Mignolo, presented and explained by Adolfo S. Suarez.